Functional and structural analysis of rare SLC2A2 variants associated with Fanconi‐Bickel syndrome and metabolic traits. Issue 7 (25th April 2019) - Enogieru, Osatohanmwen J.; Ung, Peter M. U.; Yee, Sook Wah; Schlessinger, Avner; Giacomini, Kathleen M.
Abstract: Deleterious variants in SLC2A2 cause Fanconi‐Bickel Syndrome (FBS), a glycogen storage disorder, whereas less common variants in SLC2A2 associate with numerous metabolic diseases. Phenotypic heterogeneity in FBS has been observed, but its causes remain unknown. Our goal was to functionally characterize rare SLC2A2 variants found in FBS and metabolic disease‐associated variants to understand the impact of these variants on GLUT2 activity and expression and establish genotype‐phenotype correlations. Complementary RNA‐injected Xenopus laevis oocytes were used to study mutant transporter activity and membrane expression. GLUT2 homology models were constructed for mutation analysis using GLUT1, GLUT3, and XylE as templates. Seventeen FBS variants were characterized. Only c.457_462delCTTATA (p.Leu153_Ile154del) exhibited residual glucose uptake. Functional characterization revealed that only half of the variants were expressed on the plasma membrane. Most less common variants (except c.593 C>A (p.Thr198Lys) and c.1087 G>T (p.Ala363Ser)) exhibited similar GLUT2 transport activity as the wild type. Structural analysis of GLUT2 revealed that variants affect substrate‐binding, steric hindrance, or overall transporter structure. The mutant transporter that is associated with a milder FBS phenotype, p.Leu153_Ile154del, retained transport activity. These results improve our overall understanding of the underlying causes of FBS and impact of GLUT2 function on various clinical phenotypes ranging from rare to common disease. Abstract : This study uses functional assays and structural analysis to characterize pathogenic SLC2A2 variants that cause Fanconi‐Bickel syndrome (FBS). First, a table of all published FBS mutations was produced by collecting and evaluating published case reports, case series, review, and primary research articles about FBS. Next, mutations that met the following criteria were selected for functional characterization: (a) previously uncharacterized (b) missense or in‐frame indel mutations. FBS mutations that were expressed on the plasma membrane were further analyzed to determine their impact on molecular structure and dynamics using a hGLUT2 homology model built from crystal structures of hGLUT1, hGLUT3, and Escherichia coli XylE. In this analysis, we identified an in‐frame deletion variant, previously associated with a mild form of FBS, that produces a mutant transporter that retains residual activity.